Follow the Metaplasia: Characteristics and Oncogenic Implications of Metaplasia’s Pattern of Spread Throughout the Stomach - Sáenz, José B. (Frontiers in Cell and Developmental Biology, 2021)
The human stomach functions as both a digestive and innate immune organ. Its main product, acid, rapidly breaks down ingested products and equally serves as a highly effective microbial filter. The gastric epithelium has evolved mechanisms to appropriately handle the myriad of injurious substances, both exogenous and endogenous, to maintain the epithelial barrier and restore homeostasis. The most significant chronic insult that the stomach must face is Helicobacter pylori (Hp), a stomach-adapted bacterium that can colonize the stomach and induce chronic inflammatory and pre-neoplastic changes. The progression from chronic inflammation to dysplasia relies on the decades-long interplay between this oncobacterium and its gastric host. This review summarizes the functional and molecular regionalization of the stomach at homeostasis and details how chronic inflammation can lead to characteristic alterations in these developmental demarcations, both at the topographic and glandular levels. More importantly, this review illustrates our current understanding of the epithelial mechanisms that underlie the pre-malignant gastric landscape, how Hp adapts to and exploits these changes, and the clinical implications of identifying these changes in order to stratify patients at risk of developing gastric cancer, a leading cause of cancer-related deaths worldwide.